EU and Latin America. A Stronger Partnership? - Antonella Mori (Pubblicazioni ISPI, 2018)
Despite a stop-and-go policy, over the past twenty years the European Union, Latin America, and the Caribbean Region have joined forces to scale-up their partnership. Today, the time seems ripe for the EU to give new impetus to bi-regional relations as the US interest in the region appears to be decreasing, and China quickly steps in. The near future will indicate whether the political will to bolster relations between the EU and the region is actually stronger than before: how will the agreements between the EU and Mexico, Chile, and the Caribbean be updated? Will the EU-MERCOSUR Association Agreement be completed? If so, the EU will be able to enact free trade agreements with all the countries in the region, except Bolivia, Venezuela and Cuba. The latter is already involved in its first ever negotiation with the EU to strengthen bilateral cooperation. This volume provides an overview and wide-ranging analyses on the ongoing negotiations, viable options and possible results.